IMPORTANCE OF DIFFERENT METHODS TO TEACH WRITING SKILLS TO EFL LEARNERS - Oybekova Gulnoza (Zeta Repository, 2023)
The ability to write is crucial in our everyday lives as it facilitates communication within our communities. Additionally, it plays a crucial role in the development and teaching of language. As a result, teaching writing is vital, especially for those learning English as a second language in Uzbekistan. This article is devoted to clarify effective methods to teach writing skills.